Analisis Sistem Pakar Berbasis Personality dalam Implementasi Job Matching - Resmi Darni; Lativa Mursyida; Efmi Maiyana (SAINS DAN INFORMATIKA : RESEARCH OF SCIENCE AND INFORMATIC, 2022)
Absorption of vocational graduates into the world of work and industry that has not been optimal is the main focus of this research, one of the factors causing the non-optimal absorption of vocational graduates is the integration of the existing career information system with the needs of the world of work, so that the data and information obtained are not valid, practical and effective. This study aims to explain the process of designing an integrated career system that is able to recommend careers and jobs based on personality. The method used in this study is the 4D method, namely Define, Design, Development and Disseminate. The result of this study is a system application that is able to provide job recommendations based on six personality types that are useful in vocational training. The results of the model construct validation test obtained fit where, p = 0.26972 and RMSEA = 0.029, the expert validity test on aspects of Design 0.88 (Valid), Operational 0.88 (Valid), and Benefits 0.90 (Very Valid), the results practicality test 0.83 (Practical).